Thermal Evaluation of PSFB Converters Under Constant Current and Pulsed Current Charging Strategies - Karakus, Buse; Akboy, Erdem (IEEE, 2025)
Electrical vehicles have high voltage for traction and low voltage battery (LV) for light loads and emergency. Therefore, it is important to charge LV batteries to be charged full. Pulsed current (PC) charging and constant current (CC) charging are the fast-charging methods to charge batteries, rapidly. However, charging current have important effect on the temperature swings reduces lifetime of semiconductors. This study investigates the thermal behaviour of phase shifted full-bridge (PSFB) converters used in LV battery charging applications for electric vehicles under CC and PC. Moreover, different pulse frequencies are investigated to evaluate the thermal analyses. According to the results, the thermal stress (e.g. thermal cycling) of PSFB converter is significant when PC with low frequency is applied.
Keywords: constant current; electrical vehicle; pulsed current charging; thermal analysis; POWER; RELIABILITY; Energy & Fuels; Engineering